That Which Was - Patterson G. Glenn (London, Penguin Books, 2004)
Avery isn't everyone's idea of a model Presbyterian minister. A Velvet Underground fan and student of stand-up comedy, the former bank-worker can't quite get used to being 'Reverend'. Then there's his difficulty remembering biblical quotations ...Despite all this, Avery has absolute faith in his ability always to know the right thing to do. Until, that is, a man appears in his east Belfast church and confesses to murder. The only problem is - this man can't remember where, when or why he killed. Avery commits himself to finding out the truth of what happened, but if this stranger seems hampered by the limitations of his own memory, then the minister's hands are tied by his professional and personal responsibilities - and, as Avery soon realizes, neglecting his own concerns could have disastrous consequences ...